2012
DOI: 10.1039/c2gc35039d
|View full text |Cite
|
Sign up to set email alerts
|

The selective hydrogenation of biomass-derived 5-hydroxymethylfurfural using heterogeneous catalysts

Abstract: The products produced by hydrogenation of biomass-derived 5-hydroxymethylfurfural (HMF) are potential sustainable substitutes for petroleum-based building blocks used in the production of chemicals. We have studied the hydrogenation of HMF over supported Ru, Pd, and Pt catalysts in monophasic and biphasic reactor systems to determine the effects of the metal, support, solution phase acidity, and the solvent to elucidate the factors that determine the selectivity for hydrogenation of HMF to its fully hydrogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
282
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(295 citation statements)
references
References 17 publications
9
282
2
2
Order By: Relevance
“…Alamillo et al reported that Ru particles on oxide supports with isoelectric point 7 such as CeO2 catalyzed total hydrogenation of HMF to BHTHF in 1-butanol/water biphasic solvent at 403 K (maximum yield 91 %; Table 1) 28) . Ru catalysts on carbon or non-basic support gave significant amount of 1,2,5-and 1,2,6-hexanetriols, 1,2,5,6-hexanetetraol and unidentified products in addition to BHTHF.…”
Section: Ru and Pd Catalystsmentioning
confidence: 99%
“…Alamillo et al reported that Ru particles on oxide supports with isoelectric point 7 such as CeO2 catalyzed total hydrogenation of HMF to BHTHF in 1-butanol/water biphasic solvent at 403 K (maximum yield 91 %; Table 1) 28) . Ru catalysts on carbon or non-basic support gave significant amount of 1,2,5-and 1,2,6-hexanetriols, 1,2,5,6-hexanetetraol and unidentified products in addition to BHTHF.…”
Section: Ru and Pd Catalystsmentioning
confidence: 99%
“…Based on the nature of the reaction products and on what reported for furan hydrolysis [25,81] and for Achmatowicz reaction [42,76,79] a tentative reaction mechanism has been depicted (Scheme 4). It consists of an hydration of one C C double bond of BHMF followed by a dehydration that involve the hydroxymethyl group on the other side of the ring.…”
Section: Reaction Mechanismmentioning
confidence: 98%
“…In particular, furans (e.g., 5-hydroxymethylfurfural HMF) are important biomass-derived molecules which can be used as starting materials for the synthesis of a variety of potentially useful compounds [15]. The structural moieties present in HMF, allow synthetic transformations to other target molecules by means of selective reactions such as: oxidation of the formyl group [16][17][18][19][20][21][22][23], reduction of the formyl group and/or the furan ring [24][25], deoxygenation of the hydroxyl groups to 2,5-dimethylfuran [26][27][28][29], etherification and carbonylation [30][31][32][33][34][35], and hydrogenolysis transformations [36][37]. In particular, selective reduction of 5-hydroxymethylfurfural (HMF) provides access to the diol 2,5-bishydroxymethylfuran (BHMF), a valuable building block for the production of polymers and polyurethane foams [18,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selective transformations of these two functional groups with conventional reactions such as oxidation, reduction, hydrogenolysis and condensation have been widely investigated to produce chemicals and fuels 13) . For example, HMFbased diols of 2,5-bis(hydroxymethyl)furan (BHMF) 14), 15) a n d 2,5-b i s ( h y d r o x y m e t h y l ) t e t r a h y d r o f u r a n (BHMTHF) 16), 17) are candidates for biomass-derived monomer sources. HMF can also be oxidized into 2,5-diformylfuran (DFF) and/or 2,5-furandicarboxylic acid (FDCA) (Scheme 1).…”
Section: Oxidative Transformations Of Hmfmentioning
confidence: 99%